ZULFIYAKHANIM IS THE SYMBOL OF A STRONG AND INTELLIGENT UZBEK WOMAN (British Journal of Global Ecology and Sustainable Development, 2023)
This article describes the famous Uzbek poetess Zulfiyakhanim Israilova's life path, hardships and how she always stepped forward and did not stop searching despite these life difficulties. The main topics of the poet's work are discussed and proved with poetic lines. Also, the contribution of this intelligent woman to Uzbek literature and the originality of her works are highlighted.